Estudo de benchmarking do CFD gratuito openFOAM : modelagem e simulação da transferência de calor em não-equilíbrio térmico local e transiente numa frente de combustão smouldering - Pretti, Jaderson Nunes (2015)
Withconstant increaseofenergy demand it is necessary to study alternative energy sources as well as techniques to convertit into useful work on different consume scales. Another important factor is that humanity is producing more and more waste, andthere is a potential energy associatedto itthat can not be neglected. In thisscenario, combustion appearsas a good alternativefor energy recycling of waste, however, a detailed understanding of the process and the operating variables is indispensable.This paper presentsa model for the energy equations governing heat transfer in a reactive porous media of solid and gaseous phases and at the same time, simulatethe process of smouldering combustion in porous media using a free simulationsoftware, OpenFOAM, main tool used in this work.A concise description of the simulation package used is presented to the readeras well as its main characteristcs. The simulated results are compared with experimental results obtainedfromacombustion cell developed in Fuel and Combustion Laboratory of the Federal University of Espírito Santo. Finally, it isshownthe influence of physical parameters such as thickness of the front, volume fraction of solid and cooling rate in simulated temperature evolution within the bed